Ephemeroptera, Plecoptera and Trichoptera assemblages in litter in a mountain stream of the Atlantic Rainforest from Southeastern Brazil - Crisci-Bispo, Vera L. [UNESP]; Bispo, Pitágoras C. [UNESP]; Froehlich, Claudio G. (Sociedade Brasileira de Zoologia, 2007)
A fauna de Ephemeroptera, Plecoptera e Trichoptera associadas ao folhiço em um riacho do sudeste do Brasil foi estudada com o objetivo de responder às seguintes questões: 1) A riqueza e a composição faunística de EPT difere entre os dois mesohabitats (corredeira-remanso) mesmo quando associadas ao mesmo substrato, folhiço? 2) A similaridade da fauna de EPT entre os dois mesohabitas muda temporalmente? 3) A estrutura funcional de EPT difere entre os dois mesohabitats (corredeira-remanso)? Para responder essas questões, coletas mensais, de novembro de 1999 a junho de 2000, foram feitas no Ribeirão Bocaina com rede D (10 acúmulos de folhas em remanso e 10 em corredeira). A fauna de EPT do Ribeirão Bocaina foi mais diversificada e mais abundante no folhiço em corredeira do que no folhiço em remanso, no entanto, quando a riqueza foi padronizada para o mesmo número de indivíduos essa se tornou similar para as duas condições. A fauna de EPT foi bastante diferente entre os dois mesohabitats, tanto em termos da composição faunística quanto em termos funcionais. Isso provavelmente ocorreu devido às diferenças de velocidade da água, no tempo de residência do folhiço e na taxa de oxigênio da água entre os dois mesohabitats.

The study of Ephemeroptera, Plecoptera and Trichoptera associated with litter in southeastern Brazil streams aimed to answer the following questions: 1) Does richness and composition of EPT fauna differ between riffle and pool mesohabitats despite being associated to the same substratum, litter? 2) Does the similarity of the EPT fauna between both mesohabitats change with time? 3) Does the EPT functional feeding structure differ between both mesohabitats (riffles-pools)? In order to answer these questions, monthly collections, from November 1999 to June 2000, were done in Ribeirão (Stream) Bocaina with a D-net (10 litter patches in riffles and 10 in pools). The EPT fauna at Ribeirão Bocaina was more diversified and more abundant in the litter in riffles than in the litter in pools, although, when richness was standardized for the same number of individuals it became similar in both conditions. EPT fauna was very different between both mesohabitats in terms of faunal composition as well as in terms of function. Probably it was due to differences in water speed, in the time of litter residence and in the concentration of dissolved oxygen between both mesohabitats.
Comunidades de Ephemeroptera, Plecoptera e Trichoptera em folhiço de um riacho de montanha da Mata Atlântica do Sudeste do Brasil
Keywords: Ambientes lóticos; EPT; insetos aquáticos; macroinvertebrados aquáticos; Aquatic insects; aquatic macroinvertebrates; EPT; lotic environments